Escape to the beach : pre-retirement in-migrants' narratives of change, place and identity : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Sociology at Massey University, Manawatu, New Zealand - Pennell, Stella Maria (Massey University, 2016)
The pre-retirement cohort (45-65 years) that migrates within Aotearoa New Zealand remains largely ignored in social research. This cohort encompasses people experiencing an emergent mid-life life-stage characterized by increased fluidity between previously distinct phases such as work and retirement. Once relocated, in-migrants seek ways to become endogenous actors in their new locale and construct new identities. A change of habitus is required to successfully navigate the transition from city-dweller to ‘local’. One avenue to achieve this is to engage with local volunteer organisations for the development of attachment to place, identity and for the re-narration of life-meaning. This qualitative research took place in Mercury Bay on the Coromandel Peninsula, Aotearoa New Zealand, with pre-retirees who in-migrated from city locations and who sought volunteer roles in local community organisations. My initial exploration looked to understand how social capital is manifest for these individuals in their volunteer roles in their new location. Findings suggest the existence of a paradox within that development of social capital: participants’ narratives indicate that they unconsciously seek to reproduce the very conditions from which they sought to escape, as associated with urban stressors such as workplace stress, urban pressures, financial considerations, social isolation and the demands for ‘efficiency’ of new-capitalist workplaces. More particularly, the paradox plays out in the development of new forms of habitus by which participants might embed themselves within the community.
Keywords: Migration, Internal; Middle age; Lifestyles; Social aspects; New Zealand